Real-time performance analysis of modified z-source inverter-fed induction motor drives using xilinx system generator. Issue 4 (1st October 2016) - Prasad, Hanuman; Maity, Tanmoy
Abstract: This paper contributes to the performance evaluation of modified z-source inverter (ZSI) for medium voltage induction motor drives using the Xilinx System Generator. Controlling the shoot-through duty ratio of the modified ZSI, can boost the inverter output voltage during input voltage sags and maintain the desired output voltage level at the motor terminal. The proposed drive system eliminates voltage sag problem and surpasses the demerits of the traditional voltage source inverter drives. The proposed system is executed in FPGA based real-time digital simulator at fixed step solver with fixed-time step and constant switching frequency. Real-time simulation results show the performance of 225 KW, 3.3 kV induction motor for modified ZSI based adjustable speed drives during steady and dynamic states.